Nitric oxide modulation of the hypothalamo-neurohypophyseal system - Kadekaro,M. (2004)
Nitric oxide (NO), a free radical gas produced endogenously from the amino acid L-arginine by NO synthase (NOS), has important functions in modulating vasopressin and oxytocin secretion from the hypothalamo-neurohypophyseal system. NO production is stimulated during increased functional activity of magnocellular neurons, in parallel with plastic changes of the supraoptic nucleus (SON) and paraventricular nucleus. Electrophysiological data recorded from the SON of hypothalamic slices indicate that NO inhibits firing of phasic and non-phasic neurons, while L-NAME, an NOS inhibitor, increases their activity. Results from measurement of neurohypophyseal hormones are more variable. Overall, however, it appears that NO, tonically produced in the forebrain, inhibits vasopressin and oxytocin secretion during normovolemic, isosmotic conditions. During osmotic stimulation, dehydration, hypovolemia and hemorrhage, as well as high plasma levels of angiotensin II, NO inhibition of vasopressin neurons is removed, while that of oxytocin neurons is enhanced. This produces a preferential release of vasopressin over oxytocin important for correction of fluid imbalance. During late pregnancy and throughout lactation, fluid homeostasis is altered and expression of NOS in the SON is down- and up-regulated, respectively, in parallel with plastic changes of the magnocellular system. NO inhibition of magnocellular neurons involves GABA and prostaglandin synthesis and the signal-transduction mechanism is independent of the cGMP-pathway. Plasma hormone levels are unaffected by icv 1H-[1, 2, 4]oxadiazolo-[4,3-a]quinoxalin-1-one (a soluble guanylyl cyclase inhibitor) or 8-Br-cGMP administered to conscious rats. Moreover, cGMP does not increase in homogenates of the neural lobe and in microdialysates of the SON when NO synthesis is enhanced during osmotic stimulation. Among alternative signal-transduction pathways, nitrosylation of target proteins affecting activity of ion channels is considered.